Rxprep course book : a comprehensive course for the NAPLEX & CPJE - Shapiro, Karen; Brown, Sherry A. ([Place of publication not identifed] : RxPrep, 2013)
Completely updated for 2013, the RxPrep Course Book is the preferred study guide for students preparing for the NAPLEX(R) exam and/or the CPJE. Features include: Expanded Infectious Diseases; Expanded Common Skin Conditions; Expanded IV Drugs, Fluids, Antidotes; Additional Calculation Practice for Math & Biostatistics; All New Essential Drugs & Updates including COPD, Pain, Weight Loss, and others. Includes practice cases for many major therapeutic topics.
Includes index.
Keywords: PHARMACY EXAMINATIONS